Variability in Design and Materials of Vaginal Stent or Moulds for Vaginal Agenesis - A Systematic Review - Prachi Jain; Shreya Jain; Arush Bansal; Abhinandan Soni (Wolters Kluwer Medknow Publications, 2024)
Background: Vaginal stents play a crucial role in both non-surgical and surgical management of vaginal agenesis. Different types of stents with variable designs and materials have been described in the literature. However, a summary of various stents described in the existing data and their outcome measures needs to be studied. Objectives: The objective of the study was to identify and summarise different types of vaginal stents used for patients with vaginal agenesis, to identify the design and material of different vaginal stents and to assess the benefit of using that specific vaginal stent. Materials and Methods: The literature search was conducted in the PubMed database for articles from 2000 to 2024 in the English language. An exploration of grey literature was also included through Google Scholar. The articles were included only if they clearly described vaginal stent, its material, design and advantage of using that particular stent, and any study not directly related to the research question or in which vaginal stent was used for cases other than vaginal agenesis/Mayer-Rokitansky-Kuster-Hauser syndrome/Mullerian aplasia or agenesis were not included in this study. Risk of bias assessment was done using an eight-item tool that included domains of selection, ascertainment, causality and reporting. Results: A total of 133 abstracts appeared in PubMed, of which, 26 titles/abstracts were related to the research question. Based on inclusion and exclusion criteria, seventeen articles were selected for the review. A total of 905 articles were identified from Google Scholar, of which, 7 were chosen to be included. The literature reports the usage of variable vaginal stents which can be hard, soft, solid or hollow with the option of customisation available. Interpretation: Based on the results of this review, soft stents are better than rigid stents due to increased patient compliance, a critical factor contributing to the success of the treatment. The resilient nature, comfort and lightweight of the silicone material are more suitable than commonly used acrylic material. However, the choice in a particular case may vary. Limitations: The majority of articles included in this review were case reports. As the duration and frequency of usage of stents affect the outcome, studies need to be done to evaluate the effectiveness of different types of stents to come to identify the best design and material for vaginal stents. PROSPERO Registration: CRD42024554676.